1987
DOI: 10.1136/thx.42.4.285
|View full text |Cite
|
Sign up to set email alerts
|

Use of radionuclide scanning in the preoperative estimation of pulmonary function after pneumonectomy.

Abstract: Twenty eight patients with bronchial carcinoma were studied before pneumonectomy. Measurement of spirometric indices, static lung volumes, transfer factor (TLCO), and transfer coefficient (Kco) was undertaken before and four months after pneumonectomy. Fourteen of the patients also performed a symptom limited progressive exercise test on a cycle ergometer before and four months after pneumonectomy. All patients had standard xenon-133 ventilation and technetium-99m perfusion scans performed before operation. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0
16

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 20 publications
(2 reference statements)
0
54
0
16
Order By: Relevance
“…In 1987, CORRIS et al [124] and, recently, PUENTE-MAESTU et al [125], showed that using Olsen's perfusion scan formula they were able to predict postoperative exercise capacity (V 'O 2 ,max-ppo). At our institution, BOLLIGER et al [48] recently studied a group of 25 patients with impaired pulmonary function using this formula to predict V 'O 2 ,max-ppo; and very good correlations were found between predicted and measured postoperative values.…”
Section: Split-function Studiesmentioning
confidence: 99%
“…In 1987, CORRIS et al [124] and, recently, PUENTE-MAESTU et al [125], showed that using Olsen's perfusion scan formula they were able to predict postoperative exercise capacity (V 'O 2 ,max-ppo). At our institution, BOLLIGER et al [48] recently studied a group of 25 patients with impaired pulmonary function using this formula to predict V 'O 2 ,max-ppo; and very good correlations were found between predicted and measured postoperative values.…”
Section: Split-function Studiesmentioning
confidence: 99%
“…5 However, reaching a definitive conclusion about predicting postoperative pulmonary function was difficult in most of these studies because they were based on small samples and short monitoring periods (3 or 6 months at the longest). [6][7][8] Furthermore, surgical techniques and postoperative care have steadily improved since these studies were performed.…”
Section: Introductionmentioning
confidence: 99%
“…If these requirements are not met, a perfusion or ventilation scan is performed, and the predicted postoperative FEV1 (FEV1,ppo) is estimated. The accuracy of these methods is proven [7][8][9][10][11] and it seems generally accepted that a FEV1,ppo of 0.8-1.0 L or 30% pred represents the lower limits of acceptable risk [4][5][6][12][13][14][15][16][17]. Some recommend different limits for different resections [18].…”
mentioning
confidence: 99%